Optimal low‐density lipoprotein concentration for cardiac allograft vasculopathy prevention. Issue 5 (7th May 2018) - Harris, Justin; Teuteberg, Jeffery; Shullo, Michael
Abstract: Cardiac allograft vasculopathy (CAV) is a major risk factor influencing graft loss and patient survival following orthotopic heart transplant. Allograft vasculopathy is a multifactorial process, which includes both immunologic and non‐immunologic mechanisms. Given the non‐immunological risk factors for vasculopathy, particularly hyperlipidemia, it is intuitive that reducing a patient's LDL would help attenuate the disease process. Multiple studies have shown benefits with the use of statin therapy. However, current heart transplant guidelines do not give a specific recommendation as to what LDL goal should be achieved in this patient population. This study is a retrospective cohort analysis designed to determine the relative risk of developing cardiac allograft vasculopathy with respect to different LDL goals. Median LDL level of <100 mg/dL was shown to significantly reduce the risk of developing cardiac allograft vasculopathy. Twelve of 37 patients with an LDL ≥100 mg/dL (32.4%) developed CAV vs 25 of 157 patients (15.9%) with an LDL <100 mg/dL ( P  = .021). Furthermore, a delay in to time to cardiac allograft vasculopathy was seen when a median LDL concentration of <100 mg/dL was achieved. This benefit was not extended when a goal concentration of <70 mg/dL was targeted.